Laudato Si, Environmental Theology and the Leadership of Pope Francis - Kriswibowo, Arimurti; Amtiran, Abdon (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article explores the interaction between environmental theology and leadership in the context of Pope Francis'